Changing cartographies of health in a globalizing world (Medicine Anthropology Theory, 2014)
Anthropologists have described, often in eloquent detail, local destruction of opportunities to lead a healthy life (the social determinants of health) attendant on the macroscale economic processes conveniently described as ‘globalization’. Recent reorganizations of production and finance redraw maps both literal and metaphorical of the inequalities that affect health. I argue that it is essential to focus attention on the common origins of such local destructions in new modalities and power structures of global capitalism, and in doing so to focus on what William Robinson has described as a shift from ‘territorial’ to ‘social cartographies’. These include a number of cross-border ‘emerging markets’ or bidding wars that are relevant to health and its social determinants. The article sets out three propositions about how the social science of health disparities should respond to globalization, emphasizing possibilities for research on globalization and health that draw on the complementary perspectives of anthropology and political economy.